2004
DOI: 10.1002/ppul.20047
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D levels in children with cystic fibrosis

Abstract: Osteopenia is increasingly recognized in adults with cystic fibrosis (CF), and is potentially related to vitamin D deficiency in both adulthood and childhood. Vitamin D supplements are recommended and prescribed to all pancreatic-insufficient patients. We aimed to ascertain whether vitamin D deficiency in children with CF was prevalent. 25-hydroxyvitamin D (25-OHD) was measured in 290 children attending a specialist pediatric CF clinic for annual assessment. 25-OHD levels were compared with reference values an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 11 publications
5
36
1
Order By: Relevance
“…Other studies have examined the prevalence of vitamin D deficiency in CF and examined its association with FEV 1 cross-sectionally. Similar to our results, most of these studies have found no association between vitamin D deficiency and FEV 1 (10,12,23,37). We did, however, see a linear relationship between vitamin D level and FEV 1 in the adolescent age group.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Other studies have examined the prevalence of vitamin D deficiency in CF and examined its association with FEV 1 cross-sectionally. Similar to our results, most of these studies have found no association between vitamin D deficiency and FEV 1 (10,12,23,37). We did, however, see a linear relationship between vitamin D level and FEV 1 in the adolescent age group.…”
Section: Discussionsupporting
confidence: 80%
“…We did, however, see a linear relationship between vitamin D level and FEV 1 in the adolescent age group. The former studies may not have seen a linear relationship, as they did not adjust for age, and two had a mean age of 9 and 11 years, younger than the adolescent population with significant findings in our study (12,37). In the third study, 81% of patients were vitamin D deficient or insufficient and may not have had enough patients with 25-OHD levels greater than 30 mg/L to see a significant trend.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…As a natural consequence, all nutritional guidelines insist on preventing this deficiency by means of a daily oral supplement (Borowitz et al, 2002;Sinaasappel et al, 2002;Aris et al, 2005). Data on serum concentrations of 25-OH cholecalciferol (25 (OH) D) in CF are, however, not unequivocal, as they have been reported as too low by some authors (Donovan et al, 1998;Mortensen et al, 2000;Rovner et al, 2007), whereas others disagree (Buntain et al, 2004;Chavasse et al, 2004). Moreover, the failure of oral supplement treatments is common and has been widely published (Donovan et al, 1998;Boyle et al, 2005;Green et al, 2008;Green et al, 2010).…”
Section: Introductionmentioning
confidence: 89%